Learning by Consuming: Human Capital Consumption as an Approach to Compensating Economic Efficiency. Issue 12 (26th September 2022) - Li, Zhaochen; Yuan, Fuhua; Zheng, Jinghai; Hu, Angang
ABSTRACT: As economic development moves to the stage of urbanization and knowledge-orientation, consumption is increasingly important for economic efficiency. This study proposes a Learning by Consuming Model which divides consumption into daily consumption and human capital consumption, combing consumption and human capital to measure consumption's effect on economic efficiency. We compare trends in international consumption and conduct empirical tests using a fixed effects model based on panel data for 118 countries from 1970 to 2019. The results suggest that consumption can be regarded as an approach of human capital accumulation, thereby improving economic efficiency and leading to increased growth. Human capital consumption is key to growth model's transition to the developed economy.